Five new species of Tupiperla Froehlich, 1969 (Plecoptera: Gripopterygidae) - Duarte, Tácio; Novaes, Marcos Carneiro; Bispo, Pitágoras Da Conceição (Zootaxa, 2019)
The stoneflies of the family Gripopterygidae have a Gondwanan distribution (Australian, Neotropical, and Andean regions) and include about 300 species in five recognized subfamilies. The subfamily Gripopteryginae is restricted to the Neotropics and the Andean regions of South America, including 15 genera and about 80 species. Tupiperla Froehlich, with 20 species, is the largest genus among the South American Gripopteryginae. The genus has been recorded from Brazil, Paraguay, and northeastern Argentina. In Brazil, Tupiperla has been recorded from southern, southeastern, and the mountainous areas of central and northeastern, primarily from streams of the Atlantic Forest. We studied specimens of Tupiperla collected from the Atlantic Forest of southern Brazil. Herein, five new species of Tupiperla are described: T. pinhoi sp. nov., T. serrulata sp. nov., T. pessacqi sp. nov., T. ubuntu sp. nov., and T. zwicki sp. nov.